Mathematical Modeling of Complement Pathway Dynamics for Target Validation and Selection of Drug Modalities for Complement Therapies - Bansal, Loveleena; Nichols, Eva-Maria; Howsmon, Daniel P.; Neisen, Jessica; Bessant, Christina M.; Cunningham, Fraser; Petit-Frere, Sebastien; Ludbrook, Steve; Damian, Valeriu (Frontiers in Pharmacology, 2022)
Motivation: Complement pathway plays a critical role in innate immune defense against infections. Dysregulation between activation and regulation of the complement pathway is widely known to contribute to several diseases. Nevertheless, very few drugs that target complement proteins have made it to final regulatory approval due to factors such as, high concentrations and dosing requirements for complement proteins and serious side effects from complement inhibition. Methods: A Quantitative Systems Pharmacology (QSP) model of the complement pathway has been developed to evaluate potential drug targets to inhibit complement activation in autoimmune diseases. The model describes complement activation via the alternative and terminal pathways as well as the dynamics of several regulatory proteins. The QSP model has been used to evaluate the effect of inhibiting complement targets on reducing pathway activation caused by deficiency in factor H and CD59. The model also informed the feasibility of developing small molecule or large molecule antibody drugs by predicting the drug dosing and affinity requirements for potential complement targets. Results: Inhibition of several complement proteins was predicted to lead to a significant reduction in complement activation and cell lysis. The complement proteins that are present in very high concentrations or have high turnover rates (C3, factor B, factor D and C6) were predicted to be challenging to engage with feasible doses of large molecule antibody compounds (≤20mg/kg). Alternatively, complement fragments that have a short half-life (C3b, C3bB, C3bBb) were predicted to be challenging or infeasible to engage with small molecule compounds due to high drug affinity requirements (>1nM) for inhibition of downstream processes. The drug affinity requirements for disease severity reduction were predicted to differ more than 1-2 orders of magnitude than affinities needed for the conventional 90% target engagement (TE) for several proteins. Thus, the QSP model analyses indicate the importance for accounting for TE requirements for achieving reduction in disease severity endpoints during lead optimization stage.